Pengelolaan Usaha Tiram Bakar dalam Meningkatkan Pendapatan Ekonomi Keluarga di Lajari Kabupaten Barru - Dwi Aini Azzarah; Agus Syam; Nurjannah Nurjannah; Nurdiana Nurdiana; Ratnah Ratnah (Ideas Publishing, 2023)
The purpose of this study was to determine the financial condition of the baked oyster business actors and the application of administrative functions in managing the oyster business in Lajari, Barru Regency to increase family financial income. This study uses a qualitative approach, collecting data through observation, interviews and documentation. The survey results show that the management of the grilled oyster business in Lajari, Barru Regency, is growing every year, so that the income of the grilled oyster entrepreneur s family has increased, and the business manager has implemented a business management function and management strategy, so that grilled oysters develop and are known by many people and last until at the moment.